Intangible cultural heritage in fine arts curriculum in Chinese secondary school: a systematic literature review and implications on pre-service teacher education / Zeng Yance, Harrinni Md Noor and Muhammad Faiz Sabri - Zeng, Yance; Md Noor, Harrinni; Sabri, Muhammad Faiz (Universiti Teknologi MARA, 2025)
In recent years, Intangible Cultural Heritage (ICH) has received widespread attention as an expression of cultural diversity and a representation for maintaining national cultural identities. It has been widely used as a resource for teaching and learning in the curriculum. China, being one of the countries with the largest repository of intangible cultural heritage, has attracted the interest of educators in many regions to this endangered yet rich and brilliant heritage. As curriculum resource research has emerged, the study of ICH as a curriculum resource has gradually become a popular topic in education research across various disciplines, including fine arts education. Although there is extensive literature exploring the application of ICH in fine arts education in secondary schools in China, there is no systematic review that summarizes these teaching methods and practices. Therefore, this research aims to explore the pedagogical applications of ICH in the fine arts curriculum in secondary schools in China, identifying the current types of ICH as course resources, curriculum designs, teaching methods and practices, future challenges as well as potential recommendations, and research perspectives. Utilizing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, an exhaustive search was conducted across three multidisciplinary databases from 2019 to 2023 with specified inclusion and exclusion criteria. This systematic review further reveals the significance of ICH as a valuable educational resource that fosters cultural identity, critical thinking, and creative expression, while also offering critical insights for enhancing pre-service fine arts teacher education to effectively integrate ICH into their teaching practices.